Analysis of the urban territorialities in the intervention designs for the approach of adolescents living on street - Daniel A. Fagundez D'Anello; Ayudante grado 2 - Instituto de Psicología Social - Facultad de Psicología - Universidad de la República Oriental del Uruguay (Escuela de Psicología, Pontificia Universidad Católica de Valparaíso, 2018)
Urban transformations can affect the problem of people living in the streets. The objective of this study was to understand, from the perspective of the Actor Network Theory, how the transformations of the urban assemblages of the city of Montevideo act on the problem of adolescence in street situations. Through an ethnographic study, the relationships between these adolescents, the social operators, the policy makers and the non-human entities involved in the production of the problem were analyzed. The ethnography was carried out between 2013 and 2016, together with a program of intervention on the street and in its work establishment, added to the official documentary analysis of the problem in Uruguay. The analysis was made from the studies of the actor-network theory and the theory of urban assemblages. The results indicate that the urban changes in the territory of intervention of this team were decisive to understand the transformation of the problem of extreme street situation of adolescents. It was also visualized that social operators are key informants to account for how these changes happen. These results are discussed with studies from different parts of the world, including in a novel way the analysis from the concept of urban assemblages and the actor network theory.